(3JXgjQ GdChQGb GdJLGQjI (B:s (3OQGSI ebGQfI aj GdbGfhfjf GdGQOfj hGdeUQj hGJaGbjI Lfja GdehMOI (B1930 /s - (3GdWQGhfI, HSGe MeOs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2004)
(3GdWHjYI GdbGfhfjI dJXgjQ GdGhQGb GdJLGQjI(B- (3CfhGY JXgjQ GdChQGb GdJLGQjI(B- (3TQhW JXgjQ GdChQGb GdJLGQjI(B- (3GdBKGQ GdbGfhfjI dJXgjQ GdGhQGb GdJLGQjI(B.s
(3GdeQGLY U(B. 339s
Keywords: (3GdCYeGd GdJLGQIs; (3GdChQGb GdJLGQjI(B- (3GdbhGfjf hGdCfXeI(B- (3GdCQOfs; (3GdbGfhf GdJLGQj(B- (3GdCQOfs